(untitled) (Indonesian Journal of Cultural and Community Development, 2024)
Background: Effective political communication strategies are crucial for enhancing public engagement. Specific Background: This study explores the qualitative communication strategies used by a local political party during the Indonesia Smart Program (PIP) scholarship distribution, contrasting it with quantitative approaches that focus on numerical data. Knowledge Gap: Existing literature lacks insights on how qualitative methods, particularly direct interviews, can inform community engagement and program visibility. Aims: The research aims to analyze DPD Golkar Sidoarjo’s communication strategies using primary interviews and secondary campaign materials. Results: Findings show that the party successfully utilized various media to increase visibility and transparency of the PIP, leading to significant community involvement through initiatives like KIPK. Novelty: This study highlights how qualitative approaches can deepen understanding of political communication’s impact on community perceptions. Implications: The increased public trust in DPD Golkar Sidoarjo indicates the effectiveness of strategic political communication in influencing electoral outcomes, revealing valuable insights into political engagement dynamics. Highlights : • Emphasizes the significance of qualitative insights for understanding community perceptions. • Highlights the effective use of media in enhancing program visibility and transparency. • Demonstrates the link between strategic communication and increased public trust and electoral support. Keywords: political communication, qualitative research, Indonesia Smart Program, community engagement, DPD Golkar Sidoarjo